PENGARUH TEKNIK RELAKSASI AUTOGENIK TERHADAP TEKANAN DARAH IBU HAMIL DENGAN PREEKLAMASIA DI KLINIK UTAMA PANASEA KABUPATEN LUMAJANG - nuri fumtidha; Tutik Ekasari; Muthmainah Zakiyyah (NHM PRESS, 2023)
The management of Preeclampsia can be done through non- pharmacological therapy, one of which is Autogenic Relaxation. Autogenic Relaxation is a self-originated relaxation technique that can improve blood flow and regulate heart rate, thus stabilizing blood pressure. The aim of this study is to determine the effect of Autogenic Relaxation Therapy on the blood pressure of pregnant women with Preeclampsia at Panasea Primary Clinic in Lumajang.This research used a one-group pretest-posttest design with a population of 50 and a sample of 50 respondents using an accidental sampling technique. Based on the study, it was found that pregnant women with Preeclampsia at Panasea Primary Clinic mostly had grade 1 hypertension, with 35 mothers (70%). Before the intervention and after receiving Autogenic Relaxation therapy, the majority of the participants had normal blood pressure, with 32 mothers (64%).The Wilcoxon test results showed a p-value of 0.000, indicating that there was a significant influence of Autogenic Relaxation intervention on the blood pressure of pregnant women with Preeclampsia at Panasea Primary Clinic in Lumajang.The Autogenic Relaxation technique performed on pregnant women with Preeclampsia can improve blood circulation, reduce stress stimuli, induce a calming effect, and stabilize blood pressure. Therefore, it can be beneficial in stabilizing the blood pressure of pregnant women with Preeclampsia.